Is Local Anesthetic Infiltration Prior to Intravenous Cannulation Beneficial to Patients? - Shrestha, Babu Raja; Shrestha, U; Shrestha, A; Rana, A (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: Intravenous cannulation causes pain, anxiety and frustration in patients along with changes in hemodynamic parameters. Infiltration of local anesthetic lessens the pain of intravenous cannulation. This study was performed to compare cardiovascular responses and verbal rating pain scores in two groups with and without local anesthetic infiltration prior to venous cannulation. Methods: This was a randomized study conducted in 100 elective surgical patients, divided into two study groups with 50 patients in each: group A (Control) and group B (local anesthetic infiltration). Prior to venous cannulation in group B, 0.5 ml of 1% lidocaine was infiltrated at the procedure site at dorsum of the wrist. Patients in group A were cannulated directly without local anesthetic infiltration. The hemodynamic changes pre and post cannulation and verbal pain rating scores were recorded by blind observers in all patients. Results: Demographic values in two groups were similar. Increase in heart rate from baseline value was significant in control group (p < 0.05). Post cannulation heart rate, systolic and diastolic blood pressure were significantly higher in group A compared to group B for the first three minutes (p < 0.05). Amongst higher number of patients in group A, verbal rating pain score was significantly higher. Ninety-four percent of the patients in group B were pain free, comfortable and satisfied with the procedure. Conclusions: Intravenous cannulation can be made pain free with patient satisfaction and hemodynamic stability if carried out with prior local anesthetic infiltration. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 10-13 DOI: http://dx.doi.org/10.3126/njog.v8i1.8853